From rosy past to happy and flourishing present: Nostalgia as a resource for hedonic and eudaimonic wellbeing. (February 2023) - Hepper, Erica G.; Dennis, Amelia
Abstract: We review recent evidence of nostalgia's ability to enhance and buffer different types of wellbeing. Nostalgia has been associated with increased hedonic wellbeing (e.g., life satisfaction, happiness) in various contexts. Nostalgia is triggered by and can mitigate against threats to hedonic wellbeing. Nostalgia also increases eudaimonic wellbeing (e.g., perceptions of vitality, environmental mastery, positive relationships) and mitigates threats to eudaimonic wellbeing through varying mechanisms. Two applications of these wellbeing benefits are being explored in recent research: nostalgia can help understand how people buffer negative psychological effects of the COVID-19 pandemic; and is being harnessed for wellbeing interventions. More experimental and longitudinal research is needed to establish and maximize the potential of nostalgia for bolstering resilience.